The Impact of Digital Marketing and Product Quality on Purchase Decisions Mediated by Brand Awareness on Vaccine Products at PT "K" Farma Group - Hotmaria, Hotmaria; Rakhman, Abdullah (Jurnal Komunikasi dan Bisnis, 2024)
This research aims to determine the impact of digital marketing and product quality on purchasing decisions of vaccine products in the PT “K” Farma Group, with brand awareness serving as a mediating factor. Especially after we have gone through the era of the Covid-19 pandemic where now we are increasingly aware of the importance of vaccines for the people. Primary data was collected using questionnaire and total sample were 82. This study used a descriptive quantitative research design. The data analysis technique uses SEM-PLS (structural equation modeling-partial least squares). This research employs data analysis technique by structural equation modeling-partial least square. Results indicated that Product and brand awareness had a significant direct positive effect on purchasing decisions, while digital marketing had a direct positive but not significant effect on purchasing decisions. Mediating Effect of Brand Awareness on Digital Marketing, Product Quality and Relationship with Purchase Decision. The study results suggest that brand awareness and perceived product quality of vaccine products to enhance purchase decisions can be proven in company "K" Pharma. Digital marketing is important but without brand awareness, the results will not be significant.